Experimental and theoretical determination of the Kα2/Kα1 intensity ratio for zinc. (January 2015) - Ito, Y.; Tochio, T.; Fukushima, S.; Taborda, A.; Sampaio, J.M.; Marques, J.P.; Parente, F.; Indelicato, P.; Santos, J.P.
Abstract: X-ray intensity ratios, such as the K α 2 / K α 1 ratio, are parameters with a large application in atomic physics and related scientific and technological areas. Despite the measurements carried out for several elements since 1969, available data are scarce for some elements. In this work, we present experimental and theoretical values for the intensity ratio K α 2 / K α 1 that were obtained within a collaboration between an experimental and a theoretical group. The value of K α 2 / K α 1 for zinc was measured using a double-crystal spectrometer. Calculations were performed within the Multiconfiguration Dirac–Fock method, including relativistic and QED corrections. Results show a very good agreement between the experiment and theory (1.2%). Abstract : Highlights: X-ray intensity ratio K α 2 / K α 1 was measured for zinc using a double-crystal spectrometer. Calculations were performed within the Multiconfiguration Dirac–Fock method, including relativistic and QED corrections. Results show a very good agreement between the experiment and theory (1.2%).